2019
DOI: 10.1002/sctm.19-0251
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcomes of infants enrolled in the first-in-human study of amnion cells for bronchopulmonary dysplasia

Abstract: We previously reported on the immediate safety and neonatal outcomes of six premature infants with severe bronchopulmonary dysplasia (BPD) who were administered human amnion epithelial cells (hAECs). One infant died in the neonatal period due to unrelated causes. In this study, we aimed to assess the long‐term safety and follow‐up outcomes of the five surviving infants until 2 years corrected age (CA). hAECs were administered intravenously at a dose of 1 × 106 cells per kilogram after 36 weeks postconceptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…A previous study reported the safety outcomes of the allogeneic administration of human UCB-MSCs, in which nine preterm infants received either a single dose of 1 × 10 7 cells/kg or 2 × 10 7 cells/kg [23]. In another single-center, open-label phase 1 trial, Lim's group administered 1 × 10 6 human amnion epithelial cells to six preterm infants with established BPD and reported the safety profile at 2 years postadministration [24,25]. In these trials, as in ours, no infusion toxicity or allogeneic UC-MSC intervention-associated adverse events were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the safety outcomes of the allogeneic administration of human UCB-MSCs, in which nine preterm infants received either a single dose of 1 × 10 7 cells/kg or 2 × 10 7 cells/kg [23]. In another single-center, open-label phase 1 trial, Lim's group administered 1 × 10 6 human amnion epithelial cells to six preterm infants with established BPD and reported the safety profile at 2 years postadministration [24,25]. In these trials, as in ours, no infusion toxicity or allogeneic UC-MSC intervention-associated adverse events were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the safety outcomes of the allogeneic administration of human UCB-MSCs, in which nine preterm infants received either a single dose of 1x10 7 cells/kg or 2x10 7 cells/kg (22). In another single-center, open-label phase 1 trial, Lim's group administered 1x10 6 human amnion epithelial cells to six preterm infants with BPD and reported the safety pro le at 2 years postadministration (23,24). In these trials, as in ours, no infusion toxicity or allogeneic UC-MSC intervention-associated AEs were recorded.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported the safety outcomes of the allogeneic administration of human UCB-MSCs, in which nine preterm infants received either a single dose of 1x10 7 cells/kg or 2x10 7 cells/kg (23). In another single-center, open-label phase 1 trial, Lim's group administered 1x10 6 human amnion epithelial cells to six preterm infants with established BPD and reported the safety pro le at 2 years postadministration (24,25). In these trials, as in ours, no infusion toxicity or allogeneic UC-MSC intervention-associated adverse events were recorded.…”
Section: Discussionmentioning
confidence: 99%